2009
DOI: 10.1002/anie.200901550
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Confinement of Single Cells of Bacteria in Small Volumes Initiates High‐Density Behavior of Quorum Sensing and Growth and Reveals Its Variability

Abstract: One is a quorum: As few as one to three cells of Pseudomonas aeruginosa bacteria are confined in small volumes by the use of microfluidics. These small numbers of cells are able to activate quorum sensing (QS) pathways and achieve QS‐dependent growth. The results also show that at low numbers of cells, initiation of QS is highly variable within a clonal population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
232
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(246 citation statements)
references
References 40 publications
11
232
1
2
Order By: Relevance
“…We note that a very recent study of QS in Pseudomonas aeruginosa also found variability in the onset of QS in small clusters confined in microwells, with some cells evidently not initiating QS in this environment [16]. In our experiment, by contrast, all chambers that contained visible cells eventually displayed an onset of QS.…”
Section: Discussioncontrasting
confidence: 46%
“…We note that a very recent study of QS in Pseudomonas aeruginosa also found variability in the onset of QS in small clusters confined in microwells, with some cells evidently not initiating QS in this environment [16]. In our experiment, by contrast, all chambers that contained visible cells eventually displayed an onset of QS.…”
Section: Discussioncontrasting
confidence: 46%
“…As a result, several new phenomena emerge due to crosstalk between spatially segregated populations [6]. Consequently, it appears that AI molecules can be an indicator of increased local population density, and can also be proxies of other variables, such as population dispersal [7][8][9][10][11].In recent years, advances in the ability to experimentally probe the properties of cellular populations at the single-cell level [12] have resulted in a growing community of theoretical physicists working to catalogue the different classes of collective behavior found in interacting communities of organisms [13][14][15][16][17]. This approach has already successfully yielded insight into a wide variety of ecological problems, with notable recent examples including the effects of invasion in cooperative populations [18], optimal foraging strategies in sheep herds [19], and the properties of microbial signal transduction net-…”
mentioning
confidence: 99%
“…As a result, several new phenomena emerge due to crosstalk between spatially segregated populations [6]. Consequently, it appears that AI molecules can be an indicator of increased local population density, and can also be proxies of other variables, such as population dispersal [7][8][9][10][11].…”
mentioning
confidence: 99%
“…The capillary electrophoresis system was automatized to analyze $3.5 cells/min. [4][5][6][7][8][9][10] Compared with these methods, the droplet based technology is attractive [11][12][13][14][15][16][17][18][19][20][21] because of its ultra high throughput cell encapsulations ($1000 droplets/s) [22][23][24] and accurate fluidic controls. Accordingly, a wide range of droplet base single cell polymerase chain reactions (PCR) were carried out in previous studies.…”
mentioning
confidence: 99%